The Effectiveness of Cold Compress on Reducing Edema in Post-Filler Procedure Patients at the Aesthetic Lounge - Devita Angraeni; Siti Aminah (Eduvest - Journal of Universal Studies, 2026)
This study aims to evaluate the effectiveness of cold compress on reducing edema in patients post facial filler procedures at Aesthetic Lounge Clinic. Edema is a common side effect following filler procedures, which can affect the patient's appearance. This research employed a pre-experimental design using the one group pretest-posttest method. Seventy patients who experienced edema after filler procedures were given a cold compress intervention for 10-15 minutes. The results showed that cold compress significantly reduced edema, both in scale and size. The Wilcoxon Signed Rank Test yielded a p-value < 0.05, indicating a significant difference between the edema conditions before and after the intervention. The findings conclude that cold compress is an effective non-invasive intervention for reducing post-filler edema, with additional benefits of easy application and low cost.